Enhancement of anammox bacterial activity by sodium glutamate. (April 2020) - Xu, Xianglong; Liu, Guo-hua; Zhao, Dongmei; Chen, Jinhui; Shao, Yuting; Wang, Jian; Zhou, Kai; Li, Qinyu; Wei, Qi; Wang, Hongchen
Abstract: In this paper, the enhancement of sodium glutamate (SG) on activity of anaerobic ammonia oxidizing (anammox) bacteria was investigated by batch tests. The results illustrated that SG played an important role in enhancing anammox bacterial activity when the SG dosage ranged from 0.50 to 1.25 mM, and the optimal SG concentration was 1.00 mM. The performance of anammox was the best and the total nitrogen removal rate (TNRR) was 138.2 mg N g −1 ·VSS·d −1 when the concentration of SG was 1.00 mM. The results of EPS and anammox bacterial biomass measurement indicated that protein (PN), polysaccharide (PS), total EPS and the bacterial abundance reached the maximum of 1.00 mM SG addition. Compared to the control tests, the EPS content and bacterial abundance increased by 38.2% and 75.8%, respectively. In addition, the cloning results showed that the community structure of anammox bacteria evolved in species level of Candidatus Brocadia genus under the condition of SG enhancement. Highlights: The appropriate SG dosage can enhance the activity of anammox bacteria. The TNRR was increased by 49.5% when the SG dosage was 1.0 mM. Supplementary SG can accelerate EPS secretion and the anammox bacterial growth. The dominant anammox bacteria were Candidatus Brocadia fulgid after adding SG.